Virtual Reality Media: The Simulation of Relativity Theory on Smartphone - Dadan Sumardani; Agustiani Putri; Rahma Rosaliana Saraswati; Dewi Muliyati; Fauzi Bakri (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2020)
Learning physics science is ideally accomplished through the experiments, although the theory of special relativity is challenging to understand. It is difficult because this topic has not occurred in real experience, and no technology has launched at the speed of light. To understand this theory, Virtual Reality (VR) can potentially visualize the actual concept of relativity by presenting an artificial environment to the students. The aim of this research is to develop the virtual reality application as a learning media for special relativity. This Research and Development uses the Lee and Owens Model, which consists of analysis, design, development, implementation, and evaluation. The system development method used is black-box testing. The result of the development of this system is the creation of a VR application to explain the material of relativity. From the results of black-box testing, the test results show that the percentage of application system success is 83%, which indicates that the application is functioning correctly on smartphone usage so that this application can be used on the theory of relativity simulation users using virtual reality devices.